2007
DOI: 10.1183/09031936.00094707
|View full text |Cite
|
Sign up to set email alerts
|

Measuring inspiratory muscle strength in neuromuscular disease: one test or two?

Abstract: Inspiratory muscle strength monitoring is crucial in patients with neuromuscular disorders. The sniff nasal inspiratory pressure (SNIP) and maximal inspiratory pressure (PI,max) are usually measured. The present study investigated whether the test yielding the best value at baseline continued to yield the best value during follow-up.The present study included 25 patients with Duchenne muscular dystrophy (DMD) and 61 with myotonic muscular dystrophy (MMD). SNIP and PI,max were measured at baseline and then annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 27 publications
0
29
0
4
Order By: Relevance
“…Percebe-se que, embora os resultados desta e de outras investigações mostrem semelhanças entre os valores médios de PImáx e SNIP, essas medidas avaliam de forma distinta os músculos inspiratórios, confirmando a complementaridade, relatada pela literatura 15,25,29 . Além disso, a respeito da precisão de diferentes testes na detecção da fraqueza muscular respiratória, a associação das medidas de PImáx e SNIP contribui para a redução de falsos diagnósticos de fraqueza dos músculos inspirató-rios 30 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Percebe-se que, embora os resultados desta e de outras investigações mostrem semelhanças entre os valores médios de PImáx e SNIP, essas medidas avaliam de forma distinta os músculos inspiratórios, confirmando a complementaridade, relatada pela literatura 15,25,29 . Além disso, a respeito da precisão de diferentes testes na detecção da fraqueza muscular respiratória, a associação das medidas de PImáx e SNIP contribui para a redução de falsos diagnósticos de fraqueza dos músculos inspirató-rios 30 .…”
Section: Discussionunclassified
“…Dessa forma, o sniff teste corresponde a um esforço natural que muitos pacientes acreditam ser de mais fácil realização quando comparado ao esforço preciso para desempenhar uma manobra estática, como a PImáx 9,10,15 . Apesar da influência das disfunções respiratórias, principalmente as relacionadas à força dos músculos respiratórios, sobre pacientes neurológicos, ainda existem lacunas no conhecimento a esse respeito.…”
Section: Introductionunclassified
“…The maneuver performance is simpler than MIP, since there is less need for coordination between the end of expiration and fitting with the mouthpiece 9 . Despite some similarities between maneuvers to obtain MIP and the sniff test, the limits of agreement between them are large, indicating that these measures are not interchangeable and therefore are considered complementary for inspiratory muscle strength assessment 24,25 . Findings in this study showed no significant difference between the means assessed by both equipments.…”
Section: Discussionmentioning
confidence: 99%
“…La polisomnografía es un examen adecuado para estudiar las condiciones fisiológicas del paciente en el sueño, sin embargo es de alto costo, requiere mucho tiempo y no es posible hacerla durante una consulta de rutina (2) . La espirometría y la pimometría son pruebas validadas para evaluar el estado basal y el seguimiento de estos pacientes (6)(7)(8)(9) . El ultrasonido(US) aparece como una técnica simple y no invasiva que permite la caracterización morfológica del diafragma a través del modo B y la evaluación de sus movimientos mediante el modo M, por lo que ayudaría a diagnosticar sus disfunciones y se podría usar para seguimientos a largo plazo (5,10,11) .…”
Section: Introductionunclassified